Strategy for implementation of manpower planning in elementary teacher education in the Republic of Korea - Lee, Bong Hi 1937- ([Quezon City s.n.], 1971)
The purpose of this study is to come up with a strategy for the implementation of manpower planning for elementary teacher education within the Long-term Comprehensive Educational Planning for the period of fifteen years (1972-1986) in the Republic of Korea. In pursuing this study effectively, documentary analysis was utilized. The data were gathered from documents and books, unpublished and published materials, reports, yearbooks, bulletins and reports. Government publications, charts and statistical data were utilized as primary sources.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Teachers, Training of -- Korea; Teachers -- Selection and appointment. -- Korea